Effects of creatine monohydrate supplementation on exercise-induced apoptosis in athletes: A randomized, double-blind, and placebo-controlled study - Rahman Rahimi; Bahman Mirzaei; Farhad Rahmani-Nia; Zivar Salehi (Journal of Research in Medical Sciences, 2015)
Background: Creatine monohydrate (CrM) has been shown to be beneficial to health due to its antioxidant potential. Strenuous exercise is associated with oxidative stress, which could lead to apoptosis. We investigated the ability of CrM in amelioration of apoptosis induced by incremental aerobic exercise (AE) to exhaustion in young athletes. Materials and Methods: In a placebo-controlled, double-blind, randomized, parallel study, 31 young athletes (age 19.52 ± 2.75 years, body mass 79.24 ± 16.13 kg, height 1.73 ± 6.49 m, body fat 16.37% ± 5.92%) were randomly assigned to CrM (4 × 5 g/day, n = 15) or placebo (PL: 4 × 5 g/day of maltodextrine powder; n = 16) to investigate the effect of 7 days CrM on serum p53 and insulin-like growth factor-1 (IGF-1) concentration after acute incremental AE test to exhaustion. Subjects performed AE before (test 1) and after 7 days of supplementation (test 2). Results: Before supplementation, AE to exhaustion induced a significant increase in serum p53 and IGF-1 concentrations at both CrM and PL groups (P < 0.05). After supplementation, serum p53 concentrations were significantly lower in CrM than PL at post-AE (P < 0.05). There were no differences in IGF-1 concentrations between CrM and PL groups at post-AE (P > 0.05). Conclusion: Our results suggest that supplementation with CrM prevents apoptosis, as measured by decreases in p53 concentration, induced by AE to exhaustion in young athletes. However, CrM had no effect on IGF-1 concentration after AE to exhaustion in young athletes.